Family firms and their role in the fall of the labor share and the rise of corporate saving in Germany - Jan Behringer; Till van Treeck; Vincent Victor (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2025)
This paper investigates the role of family firms in the fall of the labor share and rise in corporate saving in Germany from 1993 to 2019. Combining a new Family Ownership and Governance (FOG) database with financial data, we analyze 929 publicly listed firms. Our findings show that firm-level labor share declines are widespread in Germany, contrasting with findings from the U.S. that link this trend to a few fast-growing superstar firms. Family firms, particularly in manufacturing, experienced sharper decreases in the labor share and stronger increases in corporate saving compared to non-family firms. The level of family involvement in Germany's two-tier board system (management and supervisory board) further affects these outcomes. Despite paying lower wages, we find no evidence that family firms provide greater employment stability. Our results challenge global generalizations about the drivers of the labor share and corporate saving, while emphasizing the macroeconomic relevance of family firms, especially in Germany's corporate sector.
Keywords: D22; D33; G32; 330; Labor share; corporate saving; family firms